2018
DOI: 10.1051/0004-6361/201730576
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and hydrogen fractionation in high-mass star-forming cores from observations of HCN and HNC

Abstract: The ratio between the two stable isotopes of nitrogen, 14 N and 15 N, is well measured in the terrestrial atmosphere (∼ 272), and for the pre-Solar nebula (∼ 441, deduced from the Solar wind). Interestingly, some pristine Solar System materials show enrichments in 15 N with respect to the pre-Solar nebula value. However, it is not yet clear if, and how, these enrichments are linked to the past chemical history, due to the limited number of measurements in dense star-forming regions. In this respect, dense core… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
93
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 76 publications
13
93
0
Order By: Relevance
“…On the other hand, in cold dense gas, Tennekes et al (2006) derived a somewhat large ratio of 3 − 4 toward Cha-MM1. Colzi et al (2018) showed that for high-mass starless cores, the Schilke et al 1992;Talbi et al 1996). Colzi et al (2018) ratios for stronger FUV.…”
Section: N 2 H + and Ccs Abundancesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in cold dense gas, Tennekes et al (2006) derived a somewhat large ratio of 3 − 4 toward Cha-MM1. Colzi et al (2018) showed that for high-mass starless cores, the Schilke et al 1992;Talbi et al 1996). Colzi et al (2018) ratios for stronger FUV.…”
Section: N 2 H + and Ccs Abundancesmentioning
confidence: 99%
“…Colzi et al (2018) showed that for high-mass starless cores, the Schilke et al 1992;Talbi et al 1996). Colzi et al (2018) ratios for stronger FUV. However, the parameter space is not fully explored for the effects of the FUV radiation.…”
Section: N 2 H + and Ccs Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, nitriles (HCN, HNC, and CN) appear enriched in 15 N with respect to the protosolar value: Wampfler et al (2014) found A&A 644, A29 (2020) 14 N/ 15 N = 160-460 in a sample of low-mass protostars; Hily-Blant et al (2013a,b) found values of 140-360 in HCN/HNC and 470-510 in CN in prestellar cores. In high-mass star forming regions, Colzi et al (2018) found 14 N/ 15 N = 250-650. It is important to highlight, however, that all these measurements were derived using the double-isotope methods, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…We have derived the 14 N/ 15 N ratio in a sample of 87 high-mass star-forming cores, from observations of HCN(1-0) and HNC(1-0), observed with the IRAM-30m telescope (Colzi et al 2018a andColzi et al 2018b) and we have found that the ratio spans the range 100-1000, with most of the sources (25%) having values in the range 310 ¡ 14 N/ 15 N ¡ 350 (see Fig. 2 in Colzi et al 2018b), namely below the PSN value and just above the terrestrial atmosphere (TA) value (272).…”
mentioning
confidence: 99%